TRANSAKSI DIGITAL DAN PERKEMBANGAN e-TOURISM DI INDONESIA - Era Purike; Imas Wiwin Kurniasih; Fransiska Wuri Wulandari; Ayulia Nirwani (Pusat Penelitian Dan Pengabdian Masyarakat STIEPARI Semarang, 2022)
The rapid development of information technology, especially during the pandemic, has led to a significant increase in digital transactions carried out by the public. The concept of “clean, health, and safety” is included in the aspect of the payment system that minimizes physical contact in transactions, which is one of the causes of the increase in digital transactions during the pandemic. Digitalization of the payment system is considered to be the key to boosting the national economic recovery. This research uses the descriptive qualitative method. Several works of literature relevant to the research topic were used as data sources, and in-depth interviews and brief observations were conducted to obtain data. E-tourism is closely related to the development of information technology. The development of information technology has not accompanied the magnitude of digital transactions in Indonesia. There is a high correlation between the number of sites and the number of tourist visits, so the number of tourism websites in Indonesia should be increased. In addition to the added amount, it is also necessary to add digital payment features that make it easier.